The Delisting Bias in Crsp's Nasdaq Data and Its Implications for the Size Effect - Shumway, Tyler; Warther, Vincent A. (Journal of Finance, 1999)
We investigate the bias in CRSP's Nasdaq data due to missing returns for delisted stocks. We find that the missing returns are large and negative on average, and that delisted stocks experience a substantial decrease in liquidity. We estimate that using a corrected return of −55 percent for missing performance‐related delisting returns corrects the bias. We revisit previous work which finds a size effect among Nasdaq stocks. After correcting for the delisting bias, there is no evidence that there ever was a size effect on Nasdaq. Our results are inconsistent with most risk‐based explanations of the size effect.